A Homozygous Mutation in the Highly Conserved Tyr60 of the Mature IGF1 Peptide Broadens the Spectrum of IGF1 Deficiency - Keselman, Ana Claudia (2019)
Background: IGF1 is a key factor in fetal and postnatal growth. To date, only three homozygous IGF1 gene defectsleading to complete or partial loss of IGF1 activity have been reported in three short patients born small forgestational age. We describe the fourth patient with severe short stature presenting a novel homozygous IGF1 genemutation.Results: We report a boy born from consanguineous parents at 40 weeks of gestational age with intrauterinegrowth restriction and severe postnatal growth failure. Physical examination revealed proportionate short stature,microcephaly, facial dysmorphism, bilateral sensorineural deafness and mild global developmental delay. Basalgrowth hormone (GH) fluctuated from 0.2 to 29 ng/mL, while IGF1 levels ranged from −1.15 to 2.95 SDS. IGFBP3 wasnormal-high. SNP array delimited chromosomal regions of homozygosity, including 12q23.2 where IGF1 is located.IGF1 screening by HRM revealed a homozygous missense variant NM_000618.4(IGF1):c.322T>C, p.(Tyr108His). Thechange of the highly conserved Tyr60 in the mature IGF1 peptide was consistently predicted as pathogenic by multiplebioinformatic tools. Tyr60 has been described to be critical for IGF1 interaction with type 1 IGF receptor (IGF1R). Invitro, HEK293T cells showed a marked reduction of IGF1R phosphorylation after stimulation with serum from thepatient as compared to sera from age-matched controls. Mutant IGF1 was also less efficient in inducing cell growth.Conclusion: The present report broadens the spectrum of clinical and biochemical presentation of homozygous IGF1defects and underscores the variability these patients may present depending on the IGF/IGF1R pathway activity.